2019
DOI: 10.7150/ijbs.32262
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes derived from Wharton's jelly of human umbilical cord mesenchymal stem cells reduce osteocyte apoptosis in glucocorticoid-induced osteonecrosis of the femoral head in rats via the miR-21-PTEN-AKT signalling pathway

Abstract: Purpose: Glucocorticoid-induced osteonecrosis of the femoral head (GIONFH) is a common disease after long-term or high-dose glucocorticoid use. The pathogenesis of GIONFH is still controversial, and abnormal bone metabolism caused by glucocorticoids may be one of the important factors. Exosomes, owing to their positive effect on bone repair, show promising therapeutic effects on bone-related diseases. In this study, we hypothesised that exosomes reduce osteocyte apoptosis in rat GIONFH via the miR-21-PTEN-AKT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
97
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(98 citation statements)
references
References 26 publications
1
97
0
Order By: Relevance
“…The extrinsic death receptor pathway and the intrinsic mitochondrial pathway are two major systems that could activate the expression of caspases and subsequent cell apoptosis [44]. Previous studies have reported the proapoptosis effects of excess GC on osteoblasts [45], osteocytes [46], and endothelial cells [47]. In the present study, we firstly reported that excess GC could induce EPC apoptosis through activating mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 54%
“…The extrinsic death receptor pathway and the intrinsic mitochondrial pathway are two major systems that could activate the expression of caspases and subsequent cell apoptosis [44]. Previous studies have reported the proapoptosis effects of excess GC on osteoblasts [45], osteocytes [46], and endothelial cells [47]. In the present study, we firstly reported that excess GC could induce EPC apoptosis through activating mitochondrial pathway.…”
Section: Discussionmentioning
confidence: 54%
“…Yang et al [32] performed RNA-seq and found miR-1263 prevented BMSC apoptosis in disuse osteoporosis. In a study conducted by Kuang et al, exosomes derived from human umbilical cord mesenchymal stem cells transferred miR-21 to regulate osteogenesis in GIONFH [12]. In our study, we extracted BMSCs from OVX or normal rats, and we performed miRNA-seq between BMSCs from OVX and BMSCs from OVX + exosomes groups; differentially expressed miRNAs were explored.…”
Section: Discussionmentioning
confidence: 93%
“…After rinsing, cells were xed with 4% paraformaldehyde. Mineralized nodules were observed by staining with a 1% alizarin red solution (Cyagen, Suzhou, China) following manufacturer instructions [12]. ALP staining was used to investigate the osteogenesis of BMSCs after induction [18].…”
Section: Osteogenic Differentiation Assaymentioning
confidence: 99%
See 1 more Smart Citation
“…The DiD-labeled MSC-EV distributed maximally in the liver and spleen, lesser in the bone marrow of the spine, femur, and tibia, and were undetectable in the lung, heart, and kidney (Wen et al, 2019). PKH-26A, a lipophilic dye that integrates into cell membranes, is commonly used to label MSC-EV (Bucan et al, 2019;Karaoz et al, 2019;Kuang et al, 2019). Bucan et al (2019) evaluated the effects of rat adipose-derived MSC-EV (rAMSC-EV) on sciatic nerve regeneration and neurite growth.…”
Section: Biodistribution and Targeting Of Msc-ev To Target Tissuesmentioning
confidence: 99%